Oral Presentation (Mazandaran University of Medical Sciences, 2015)
Introduction: While little is known about the molecular mechanisms that establish the apical growth patterns in fungal mycelia, recent research on the genetics of A. nidulans and N. crassa has provided considerable amount information on some genes involving in polarised cell growth. A.nidulans is particularly amenable to experimental analysis and is importantly related to other human pathogen fungi that are not so easily studied such as A. fumigatus, A. niger and A. flavus.